The role of myocardial perfusion imaging in the identification of the obstructive coronary artery lesions: a tertiary cardiology center experience - Savaş, Göktuğ; Süzer Aslan, Melek; Fırat, Mehmet Fatih; Terzı, Sait (The European Research Journal, 2020)
Objectives: Because of the moderate accuracy of treadmill electrocardiogram and fear of a claim if a diagnosis is missed, cardiologists usually order Myocardial Perfusion Imaging (MPI) as a first-step test in most of patients with chest pain admitted to cardiology department. The performance of the MPI in diagnosing obstructive CAD depends on the population studied. Thus we aimed to assess the agreement between MPI and coronary angiography in the identification of the obstructive coronary lesion.Methods: A total of 231 patients who underwent MPI due to suspicion of coronary ischemia and had a coronary angiogram within the last three months were included in this retrospective study. MPI and coronary angiography findings were analyzed to weigh the performance of MPI in determining obstructive coronary lesion.Results: The mean age was 63.9 ± 8.9 years, 54.5% being males. MPI showed a sensitivity of 0.86 in determining patients who had a significant (> 70%) coronary lesion. While evaluating the ability of MPI to detect ischemia in the left ventricle region which is supplied by the lesioned vessel, the sensitivity was found to be; 60% in determining anterior ischemia associated with significant LAD lesion, 77.4% in determining inferior ischemia associated with significant RCA lesion, and 44.4% in determining lateral ischemia associated with significant CX lesion.Conclusions: Our findings have shown that MPI with visual assessment has 86% sensitivity for detecting significant coronary artery stenosis. However, the sensitivity of MPI in determining ischemia in the left ventricle region which is supplied by the lesioned coronary artery was found to be 44.4 to 77.4%.